Modeling and Thermodynamic Values of Complex Equilibrium of Cobalt(II) with Diethylenetriaminepentaacetic Acid in Aqueous Solution - Ghusoon Faidhi Hameed; Fawzi Yahya Wadday; Nahla Shakir Salman (Indonesian Journal of Chemistry, 2021)
The paper reports the study of the complex formation of cobalt (II) with diethylenetriaminepentaacetic acid (DTPA, H5L) based on spectrophotometric (SF) and potentiometric data (pH). Complexes of different compositions were found, and equilibrium constants, as well as the stability constants of these complexes, were determined. Accumulation of complexes in proportion is calculated based on the acidity of the medium. The experimental data have been carried out by using mathematical models to assess the solution's possible existence with a wide spectrum of complex particles and to point out those which are quite sufficient to copy the experimental data. In addition, thermodynamic parameters (ΔG°, ΔH°, and ΔS°) for the studying complexes were calculated according to the values of stability constant (KST) at 25 °C obtained from the temperature dependence of stability constant by using van’t Hoff equation.